Construction of Bi2Fe4O9/red phosphorus heterojunction for rapid and efficient photo‐reduction of Cr(VI). Issue 10 (31st March 2021) - Zhu, Enquan; Zhao, Shuxian; Du, Hong; Ma, Yuhua; Qi, Kezhen; Guo, Cangchen; Su, Zhi; Wang, Xin; Wu, Zhende; Wang, Zhuanhu
Abstract: Construction of heterojunctions with matching energy band structures between two semiconductors displays great potential in promoting the separation and transfer of photogenerated charge carriers and is one of the effective strategies for obtaining high active photocatalysts. In this study, a type‐II heterojunction photocatalyst was designed and prepared using Bi2 Fe4 O9 (BFO) nanoparticles and hydrothermal‐treated red phosphorus (HRP). The photocatalytic performance test exhibited that the 3%BFO/HRP composite photocatalyst with 3% mass fraction of BFO rapidly and efficiently photoreduced Cr(VI), and the reduction was completed within 25 min, with a rate constant of 0.15 min −1, which was 15 times higher than that of pure HRP. Further mechanistic investigation revealed that the photocatalytic activity was enhanced due to the tight heterojunction between BFO and HRP, thereby effectively promoting carrier transfer, destroying the carrier recombination, and reducing the charge‐transfer resistance of composite catalyst. Mott–Schottky diagrams and UV‐vis diffuse reflectance spectroscopy data indicated the theoretical feasibility of establishing a close contact between BFO and HRP. X‐ray photoelectron spectroscopy provided evidence for the way in which interfacial charges were transferred. This work provides a new possibility to construct heterojunction photocatalysts for the rapid and efficient reduction of Cr(VI). Abstract : Bi2 Fe4 O9 /HRP heterojunction photocatalyst exhibited super photoreduction activity for Cr(VI), due to the tight heterojunction between Bi2 Fe4 O9 and HRP, which can effectively promote carrier transfer, destroy the carrier recombination and reduce the charge transfer resistance of composite catalyst.